Families’ and Residents’ Perspectives of the Quality of Nursing Home Care: Implications for Composite Quality Measures - Mukamel, Dana B. (J Am Med Dir Assoc, 2020)
OBJECTIVES: To assess (1) the relationship of consumers’ assessment of overall nursing home quality to their assessment of specific dimensions of quality; and (2) the implications of this relationship for composite quality measures in Nursing Home Compare. DESIGN: A survey conducted in 2017 elicited respondents’ assessments of the quality of overall care and thirteen specific dimensions of care. SETTINGS AND PARTICIPANTS: The sample consisted of 4,449 respondents who either resided in a nursing home or had a family member who resided in a nursing home during the 6 months prior to the survey. METHODS: We estimated regression models to infer the relationship between consumers’ assessments of overall quality and 13 specific dimensions of quality. The regression coefficients, indicating the implicit importance/weight assigned by respondents to each dimension as a component of the consumers’ assessment of overall quality, were used to create a prototype composite quality measure. RESULTS: For long-stay residents, 8 of the 13 quality dimensions were significantly associated with their overall ratings of quality. Five dimensions achieved significance for short-stay residents. The magnitude of importance weights varied substantially across dimensions of care. CONCLUSIONS AND IMPLICATIONS: Our findings suggest that Nursing Home Compare could be improved by augmenting the technical information in the 5-Star composite measure with consumers’ assessments of the additional, non-technical dimensions of quality.